Influence of Perceived Distributive Justice on Affective Commitment: The Mediating Role of Perceived Supervisor Trust among UAE Government Employees - Ahmed, Ahmed Z. E.; Elamin, Abdallah M.; Aldabbas, Hazem (Journal of Posthumanism, 2025)
Although many factors affect employees’ affective commitment, its relationship with distributive justice and perceived supervisor trust is significant. Many studies have investigated the relationship between distributive justice and trust, but there is limited research on the mediating role of perceived supervisor trust. This study examines the mediating role of perceived supervisor trust in the relationship between distributive justice and affective commitment. The study’s sample comprises 168 United Arab Emirates (UAE) government employees. It is a cross-sectional study that uses a standardized questionnaire. The results reveal that distributive justice is directly related to supervisory and organizational trust, where supervisor trust partially mediates the relationship between distributive justice and affective commitment. Finally, the findings indicate that trust in the supervisor plays a crucial mediating role in the relationship between distributive justice and affective commitment, reinforcing the significance of fairness perceptions in fostering employee commitment.